Peptide density targets and impedes triple negative breast cancer metastasis - Daxing Liu (Nature Portfolio, 2018)
The C-X-C chemokine receptor type 4 (CXCR4) pathway is a key regulator of cancer metastasis. Here, the authors present a method to block CXCR4 and thereby inhibit breast cancer metastasis by developing a liposome that presents CXCR4-binding peptides in a multivalent fashion.